ARTISTIC DISCOURSE AND DISCOURSE ANALYSIS (Scientific journal of the Fergana State University, 2023)
Discourse is a broader concept than text, and consists of both the linguistic process and the text resulting from this process.  The word "discourse" is based on the understanding of all cognitive and communicative functions of speech.  It is clear that discourse is both a process and a text.  The interpretation of the text as a stable, complete product and discourse as a continuous process of verbal communication makes them very different.  In linguistic literature, the term "discourse" has no definite meaning, it is used to describe a wide range of events, from "part of the text" to the entire "speech".